Hubungan antara kadar kolesterol total dengan tekanan darah pada remaja obes - Rupang, Jason G.; Warouw, Sarah M.; Masloman, Nurhayati (e-CliniC, 2016)
Abstract: Obesity is a disorder or disease that characterized by excessive accumulation of adipose tissue. Obesity is a world health problem and increasingly common in various countries. The most common causes of obesity are genetic factors, physical inactivity, and unhealthy diet. Obesity and high total cholesterol level in adolescent cause various chronic diseases, such as diabetes mellitus, coronary heart disease, and cerebrovascular disease. The aim of this study is to investigate the correlation between total cholesterol level and blood pressure in obese adolescents. This is an analytical observational study, using cross sectional design. Samples were chose using consecutive sampling technique in two junior high schools and senior high schools in Tomohon Tengah district, Tomohon City. Samples are adolescent age 13-15 years old, which was selected through anthropometric examination, blood pressure measurement, and blood sample collection. The result from 38 samples showed that there is no correlation between total cholesterol level with blood pressure, both systolic blood pressure (p=0.867) and diastolic blood pressure (p=0.627). Conclusion: There is no correlation between total blood cholesterol and blood pressure (both systolic and diastolic). Parents should pay more attention to the childrenâ€™s health and diet to prevent a prolonged obesity.Keywords: obesity, total cholesterol, blood pressure, adolescentÂ Abstrak: Obesitas atau kegemukan adalah suatu kelaianan atau penyakit yang di tandai oleh penimbunan jaringan lemak dalam tubuh secara berlebihan. Obesitas merupakan masalah kesehatan dunia yang semakin sering ditemukan di berbagai Negara. Penyebab paling sering menyebabkan obesitas adalah faktor genetik, kurangnya aktifitas fisik dan pola makan yang tidak sehat. Obesitas dan kolesterol total yang berlebih pada remaja merupakan penyebab terjadinya berbagai penyakit kronik termasuk hipertensi, diabetes melitus, penyakit jantung koroner, dan penyakit serebrovaskular. Penelitian ini bertujuan untuk mengetahui hubungan antara kadar kolesterol total dengan tekanan darah pada remaja obes. Jenis penelitian ialah analitik observasional dengan rancangan potong lintang dengan teknik consecutive sampling pada dua SMP dan dua SMA di Kecamatan Tomohon Tengah, Kota Tomohon pada bulan September hingga November 2016. Sampel pada penelitian adalah remaja yang berusia 13-15 tahun. Data yang diambil melalui pemeriksaan antropometri, pemeriksaan tekanan darah, dan pengambilan sampel darah. Hasil penelitian dari masing - masing 38 sampel menunjukkan tidak terdapat hubungan antara kadar kolesterol total dengan tekanan darah sistolik (p=0.867) dan tekanan darah diastolik (p=0.627).Simpulan: Tidak terdapat hubungan antara kadar kolesterol total dengan tekanan darah (TDS&TDD). Orang tua diharapkan lebih memperhatikan kesehatan dan pola makan untuk mencegah terjadinya obesitas yang berkepanjangan. Kata kunci: obesitas, kolesterol total, tds, tdd, remaja